A Transaction Cost Economics View on Outsourcing Decision in Spanish Publishing Industry - Magadán-Díaz, Marta; Rivas-García, Jesús (Nordic Journal of Media Management, 2020)
Purpose: The present study analyzes, through the online survey method, the role of KIBS in the processes of digital transformation and technological change of Spanish publishing companies. The general goal of this research is to explore the effects produced over Spanish publishing companies in interacting with KIBS as facilitators, bearers, and generators of innovation. Some other more specific objectives linked to this general goal are the following ones: a) to determine the role of transaction costs as drivers of the outsourcing of knowledge management systems through KIBS; and b) to understand to what extent the interaction of publishers with KIBS promotes in those the introduction of new business models. Methodology: Through the survey conducted among 310 Spanish publishers from a universe of 992 companies pertaining to DILVE, the only platform and database of Spanish publishers used for any approach to this sector, and using open and closed questions, the study tries to answer the stated research questions. Findings/Contribution: it is concluded that: i) the extension of the relationship between publishers and KIBS moves from the production subsystem to the distribution one; ii) the link between their respective value chains is perceived as profound enough to turn KIBS into facilitators, bearers and generators of the innovation required by the Spanish publishing companies; and iii) KIBS are the fundamental axes for the adoption of new business models.